The efficacy of an adapted Roland-Morris disability questionnaire in measuring functional status of Patients with low back pain - Buchanan, Helen (Division of Occupational Therapy, 2017)
The purpose of this study was to determine whether an adapted Roland Morris Disability Questionnaire (ARMDQ) could be used to determine functional status in subjects with chronic mechanical low back pain, and thereby assist the surgeon in deciding on the appropriateness of spinal fusion surgery for individual patients. The study aimed to detem1ine whether the Roland-Morris Disability Questionnaire (RMDQ) improved its ability to measure function and different aspects of function through the addition of a 26-item scale (AddS). The study design was retrospective and descriptive. A convenience sample of 42 subjects who consulted one Orthopaedic surgeon working in a private practice in the South Peninsula Municipal area of Cape Town, South Africa, was drawn. All subjects were diagnosed with chronic mechanical low back pain and no other known pathology. Subjects consulted the surgeon between August 2000 and July 200 I. All subjects had completed the adapted RMDQ (ARMDQ). A series of analyses were performed in which the items in the AddS scale were compared with those of the RMDQ to assess the degree to which they enhanced the performance of the RMDQ. Although there was a high correlation between the two scales (R=. 72; P<.00), Cronbach's alpha showed the reliability of the RMDQ to be higher than the AddS and the ARMDQ. This finding was supported in a number of subsequent analyses. There was a low correlation between the rating for surgery and total RMDQ scores (r=.40; P<.01). Despite deficiencies in the RMDQ, it is recommended as the basis for comparison in future studies within a variety of South African contexts.